First observation of the decay B̄s0→D0K×0 and a measurement of the ratio of branching fractions B(B̄s0→D0K×0) B(B̄0→D0ρ0) - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2011)
The first observation of the decay B̄s0→D0K×0 using pp data collected by the LHCb detector at a centre-of-mass energy of 7 TeV, corresponding to an integrated luminosity of 36 pb-1, is reported. A signal of 34.4±6.8 events is obtained and the absence of signal is rejected with a statistical significance of more than nine standard deviations. The B̄s0→D0K×0 branching fraction is measured relative to that of B̄0→D0 ρ0: B(B̄s0→D0K×0) B(B̄0→D0ρ0)=1.48±0 .34±0.15±0.12, where the first uncertainty is statistical, the second systematic and the third is due to the uncertainty on the ratio of the B0 and Bs0 hadronisation fractions. © 2011 CERN.